Refuge as a Tool for Pollinator Conservation: Enhancing Biodiversity in RGL (Rimau Gerga Lebong) Citrus Orchards - Yunita Fera Rahmawati; Yuris Setyadin; Budi Purwantiningsih (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
The RGL (Rimau Gerga Lebong) citrus orchard in Malang Regency, East Java (7°55'12“ S; 112°33'45” E) was the location for this study, which focused on the problem of declining pollinator populations in fruit cultivation areas. The study aimed to analyze pollinator diversity in three types of flowering plants sunflowers (Helianthus annuus), marigolds (Tagetes erecta), and wild cosmos (Cosmos caudatus) grown around citrus orchards, while evaluating their contribution to agroecosystem stability within the framework of Integrated Pest Management (IPM). Field observations were conducted from June to December 2024 using a combination of visual censuses and sweep net methods along 100 m × 2 m transects. From the observation results, 29 pollinator species from 10 families were identified, with Apidae as the dominant group that was consistently present in all treatments. These findings indicate that planting flowering plants around RGL orange orchards could support the recovery of pollinator communities while strengthening ecosystem services in integrated agricultural systems.Refuge planting increased species richness (R = 3.87 vs. 3.40 in controls) and total pollinator abundance, although the Shannon-Wiener Index (H’) in refuge areas (1.696) was lower than in controls (2.075), attributable to the disproportionate dominance of Amata huebneri. Sunflower refuge supported the highest pollinator diversity and abundance, marigold effectively attracted Syrphidae and Meliponini stingless bees, while wild cosmos enriched Lepidoptera and solitary bee composition. Bray-Curtis cluster analysis and PCA ordination confirmed that each refuge type produced distinct qualitative shifts in pollinator community structure. This study recommends implementing multispecies refuge systems combining all three plant species proportionally to prevent single-species dominance, broaden pollinator guild diversity, and optimize integrated pollination and biological control services in RGL citrus agroecosystems.